Проблеми античної та середньовічної історії у наукових дослідженнях на навчальних курсах викладачів Чернівецького університету австрійської доби (1875 – 1914 рр.) - Чучко, Михайло Костянтинович (Науковий вісник Чернівецького національного університету імені Юрія Федьковича: Історія. Чернівці: Чернівецький університет, 2024. № 1. С.103–108, 2024)
The article is devoted to the problem of teaching courses on general history, in particular the periods of Antiquity and the Middle Ages, as well as conducting research work in this area at the Faculty of Philosophy of the University of Chernivtsi in the Austrian period (1875 – 1914). Particular attention in the study is paid to the activities in Chernivtsi of medieval historians Johann Lozert and Sigmund Herzberg Frenkel, professor of auxiliary historical disciplines, paleographer Alexander Budinsky, as well as the work of antiquarians Johann Kromayer and Oskar Leutze. Scientists J. Lozert and A. Budinsky have worked at the University of Chernivtsi since its opening in 1875. Through the efforts of Johann Lozert, who taught students a course in general history, studios in medieval studies were started in Chernivtsi. A. Budinsky founded the study of medieval paleography. At the beginning of the twentieth century Z. Herzberg-Frenkel, who studied problems of medieval history and auxiliary historical disciplines, began to teach general history at the University of Chernivtsi. In 1905/1906 was the rector of the University of Chernivtsi.Antiquities studios at the University of Chernivtsi, in particular in the direction of studying the fields of ancient battles, were developed by professor-historian J. Kromayer, who arrived from Germany. In 1911/1912 he was elected rector of the University of Chernivtsi. After J. Kromayer left for Leipzig, ancient history at the University of Chernivtsi was taught by O. Leutze from Halle, who was a specialist in the history of Republican Rome, chronology, annalistics and numismatics. The mentioned scientists left a noticeable mark on the history of the University of Chernivtsi, teaching general history there and simultaneously developing scientific topics on the problems of the history of Antiquity and the Middle Ages within the framework of the then dominant positivist methodology
. PROBLEMS OF ANCIENT AND MEDIEVAL HISTORY IN SCIENTIFIC RESEARCH AT THE COURSES OF PROFESSORS OF THE UNIVERSITY OF CHERNIVTSI IN THE AUSTRIAN PERIOD (1875 – 1914)
ЧНУ
Keywords: Чернівецький університет, викладання, навчальні курси, науково-дослідницька робота, загальна історія, медієвістика, антикознавство, палеографія, проблеми всесвітньої історії, методологія позитивізму; Chernivtsi university, teaching, training courses, research work, general history, medieval studies, ancient history, paleography, problems of world history, positivist methodology.